THE EFFECTS OF HIGH DOSE PRAVASTATIN AND LOW DOSE PRAVASTATIN AND EZETIMIBE COMBINATION THERAPY ON LIPID, GLUCOSE METABOLISM AND INFLAMMATION - Dagli, N.; Karaca, I.; Yavuzkir, M. (Elsevier Ireland Ltd, 2008)
[Abstract Not Available]